Capacity building workshop on nature-culture linkages in heritage conservation in Asia and the Pacific 2016 (CBWNCL) - Velandia Silva, César Augusto (2018)
The Coffee Cultural Landscape of Colombia (CCLC), inscribed in the UNESCO World Heritage list in 2011, is the biggest productive cultural landscape in Latin America. The CCLC is a territory where collides a complex cultural, social, productive and biodiversity facts having a national policy to its preservation. The CCLC encompasses six farming landscapes in 340,000 hectares surface, including eighteen urban settlements, in a unique sustainable and productive landscape that represents the Colombian coffee tradition. Its biodiversity is combined with the physiography of valleys and steep slopes, to the glaciers and volcanoes on the tops of ridges and native forests and biological corridors, which are strategic to the conservation of biodiversity world. Located near to the Andes, hazards are representative by Cerro Machin Volcano (CMV), a highly explosive stratovolcano, with recent activity. Evidences of CMV activity occur each 900 years, and it is expected to be as strong as eruption of Mount Pinatubo, Phillipines (June 12th, 1991).